Consumers Preference towards Various Brands of Cold Drinks among Buddhist Tamang Community in Kavresthali, Kathmandu - Tamang, Tulsi (Kaladarpan कलादर्पण, 2024)
This topic of study aims at finding out whether the consumers’ expectations of matched their satisfaction level on the basis of quality products provided by cold drinks suppliers and manufactures companies (i.e. Coca-Cola, Pepsi, Sprite, Mountain Dew and Fanta) among Buddhist Tamang Community in Kavresthali, Kathmandu. So, the research is to study the preference of the consumers and their satisfaction level. With a view to remaining competitive leading position and for businesses to grow, product quality and customer preference are key ingredients. The purpose of this study was to describe how consumers perceive product quality whether they are satisfied with product/cold drinks offered by the stated companies. The thrust of this study was to compose an assessment of product quality and consumer satisfaction of the companies. The questionnaire was developed and distributed using a convenience sampling technique among 100 respondents (Individual consumers and Retailers) within and from Buddhist Tamang Community in the Tarakeshwor Municipality 2, Kavresthali, and Kathmandu. From the analysis, it was found that the overall product quality offered by the companies Coca-Cola and Mountain Dew were relatively higher than others. Further, the analysis proved that the dependency of customer satisfaction on the quality of product and value for money were a very high positive correlation. This is why; this has been appeared that the most of the cold drinks suppliers and manufactures companies need to be very much concerned with the satisfaction of consumers by offering quality products with reasonable prices. The researcher makes a few recommendations based on the findings of the study. First of all, the management of the companies should pay attention to improve the product quality and other factors which may lead to customer satisfaction thereby improving its performance and the overall brand image and profitability of the Companies.